2020
DOI: 10.1002/celc.202000198
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐Functionalized Fe2VO4/Nitrogen‐Doped Carbon Mesoporous Nanowires with Exceptional Lithium Storage Performance

Abstract: The binary transition metal oxides have attracted great attention because of their considerable energy and power densities. However, they suffer from low reaction kinetics and large volume change, limiting their practical energy applications. The construction of a mesoporous structure with a large surface area, the development of a carbon matrix, as well as heteroatom doping can effectively overcome the above challenges. Herein, the synthesis of phosphorous‐containing Fe2VO4/nitrogen‐doped carbon mesoporous na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
3
10
0
Order By: Relevance
“…However, the conductivity would slowly decrease due to the structure deterioration, leading to further capacity decrease upon cycling. [50][51][52] Based on the above experimental results, the CoMoO 4 -N 2 exhibited excellent high-rate lithium-ion storage performance and cycling stability, which is comparable to the recently reported metal oxide electrode materials with superior electrochemical performance. [53][54][55] However, the specific capaci- ties and cycling performance of the CoMoO -Air are worse than CoMoO -N in all current densities, especially under the high rates.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…However, the conductivity would slowly decrease due to the structure deterioration, leading to further capacity decrease upon cycling. [50][51][52] Based on the above experimental results, the CoMoO 4 -N 2 exhibited excellent high-rate lithium-ion storage performance and cycling stability, which is comparable to the recently reported metal oxide electrode materials with superior electrochemical performance. [53][54][55] However, the specific capaci- ties and cycling performance of the CoMoO -Air are worse than CoMoO -N in all current densities, especially under the high rates.…”
Section: Resultssupporting
confidence: 73%
“…Along with the cycling process, the active materials would be fully utilized and transform into finer quantum dots with more active sites, resulting in the initial arise of the specific capacity. However, the conductivity would slowly decrease due to the structure deterioration, leading to further capacity decrease upon cycling [50–52] . Based on the above experimental results, the CoMoO 4 ‐N 2 exhibited excellent high‐rate lithium‐ion storage performance and cycling stability, which is comparable to the recently reported metal oxide electrode materials with superior electrochemical performance [53–55] .…”
Section: Resultssupporting
confidence: 57%
“…The CV response current ( i ) complied with the sweep rate ( v ) on the basis of the equation of i = av b , and the number of b is determined by the electrochemical behavior of the battery. When the value of b is close to 0.5, it indicates a diffusion-controlled process resulting from battery-type intercalation, whereas value b close to 1 suggests the surface-controlled capacitive storage process. , The b values of peaks 1 and 2 are evacuated to supervise the electrochemical behavior evolution under different scan rates (Figure H). With v ≤ 0.7 mV s –1 , the b values of peaks 1 and 2 are calculated to be 0.92 and 0.94, respectively, indicating that the pseudocapacitive contribution is dominating.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is reported that the crystal water and appropriate lattice defects are in favor of the rapid insertion/diffusion kinetics. 31 To compare the charge-storage kinetics in the VOH/CC and ZnVOH/CC electrodes, the diffusion coefficient D was 47,48 The b values of peaks 1 and 2 are evacuated to supervise the electrochemical behavior evolution under different scan rates (Figure 4H). With v ≤ 0.7 mV s −1 , the b values of peaks 1 and 2 are calculated to be 0.92 and 0.94, respectively, indicating that the pseudocapacitive contribution is dominating.…”
Section: Resultsmentioning
confidence: 99%
“…A high capacity of 1002 mAh g −1 at 0.5 A g −1 was obtained due to the considerable specific surface area and increased conductivity, as well as the robust structure provided by the P "bridge" between Fe 2 VO 4 and carbon sheets. 19 Despite great progress achieved in bimetallic oxides, it still remains a significant challenge to meet the overall electrochemical performance for both LIBs and SIBs. Bimetallic antimony−vanadium oxides (SbVO 4 ) possess superior electrochemical activity by virtue of their dense crystal structure, composition, interface, and active sites.…”
Section: ■ Introductionmentioning
confidence: 99%